Case Study: The Surgical Management of Angiokeratoma Resulting from Radiotherapy for Penile Cancer - Rowland Rees; Alex Freeman; Peter Malone; Giulio Garaffa; Asif Muneer; Suks Minhas (The Scientific World Journal)
Angiokeratoma is a rare, benign skin lesion and a recognised complication of radiation therapy. Here we describe a case of extensive angiokeratoma of the groin and external genitalia resulting from external beam radiation to that area in a patient with penile carcinoma. Furthermore, we outline the management of this problem by surgical reconstruction.